Um país em devir-Angola e seus narradores: a criança e o animal em Bom Dia Camaradas, de Ondjaki, e o Vendedor de Passados, de José Eduardo Agualusa - Azevedo, Vitória Albino Mendonça Bernardes de (2022)
Good Morning Comrades (2001), by Ondjaki, and The Book of Chameleons (2004), by José Eduardo Agualusa, are books that present narratives that take place in the post-colonial period in Angola, more specifically in the city of Luanda. While the first novel is narrated by a child-hero, still maturing and who did not experience the colonialist period in the country, the second storyline unfolds through the eyes of a gecko, a reclusive animal that observes each event from a privileged perspective, merging the facts of the present with its human past. Thus, the reader is invited to understand the point of view of the narrators in both works, following these becoming visions of a country in transformation. Therefore, the main purpose of this research is to analyze the function of these narrators in the selected novels, approaching historical conceptions that theoretically ground these authors’ choices and adopting the concept of becoming, developed by Deleuze and Guattari (1995; 1996; 1997 [1980]), to relate narrative elements and develop the proposed themes. To compose the discussion of the works, the assumptions of Deleuze and Guattari (1977), Deleuze and Parnet (1998 [1977]), Deleuze (1997), Garuba (2003), Machado (2009), Paradiso (2015; 2020) and Viveiros de Castro (1996; 2002) were essentially considered. Regarding the historiographical survey, we have as main theoretical contribution Heintze (2007), Wheeler and Pélissier (2016), and the great collection General History of Africa, distributed and published in Brazil by UNESCO (2010). About the methodology that conducts the work, the research is qualitative and bibliographical in nature. As a result, it is observed the analysis of deterritorialized narrators, who manifest their child and animal becoming, connecting themselves to the literary space – also in a process of becoming – and to other characters, through their positions of observation of the plot.